Molecular dynamics simulations of the effects of sodium dodecyl sulfate on lipid bilayer - 徐斌 林文强 汪小刚 曾松伟 周国泉 陈均朗 (Chinese physics B, 2017)
Molecular dynamics simulations have been performed on the fully hydrated lipid bilayer with different concentrations of sodium dodecyl sulfate （SDS）. SDS can readily penetrate into the membrane. The insertion of SDS causes a decrease in the bilayer area and increases in the bilayer thickness and lipid tail order, when the fraction of SDS is less than 28%. Through calculating the binding energy, we confirm that the presence of SDS strengthens the interactions among the DPPC lipids, while SDS molecules act as intermedia. Both the strong hydrophilic interactions between sulfate and phosphocholine groups and the hydrophobic interactions between SDS and DPPC hydrocarbon chains contribute to the tight packing and ordered alignment of the lipids. These results are in good agreement with the experimental observations and provide atomic level information that complements the experiments.